Mobile and social media journalism a practical guide for multimedia journalism - Adornato, Anthony (Routledge, 2021)
Now in its second edition, Mobile and Social Media Journalism continues to be an essential resource for learning how journalists and news organizations use mobile and social media to gather news, distribute content, and engage with audiences. Merging theory and practice, the book includes checklists and practical activities in every chapter, enabling readers to immediately build the mobile and social media skills that today's journalists need and that news organizations expect. The second edition retains a focus on journalism's core values, such as authentication, verification, and credibility, while guiding readers on how to apply them to digital media activities. The book also offers an in-depth discussion of the audience's active role in producing content, how mobile devices and social media have changed the way the audience consumes news, and what these changes mean for journalists. Updated to address the latest trends in multimedia journalism, the second edition includes two new chapters: "Writing Mobile-Friendly Web Stories" and "The Spread of Fake News". This is a valuable resource for journalism students, as well as media professionals seeking to update their skills. The book features a companion website at mobileandsocialmediajournalism.com, providing online resources for students and lecturers including video tutorials, industry news, and sample assignments. The book's Twitter account (@MobileJourn) and Facebook page (fb.com/MobileandSocialMediaJournalism) share the latest industry trends and offer tips for teaching the topic"--